MODEL PEMBELAJARAN BCCT MELALUI SENTRA SENI UNTUK MENGEMBANGKAN KREATIVITAS ANAK USIA 5-6 TAHUN DI TK ISLAMIYAH - Puteri, Sylvana; Ali, Muhamad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research focused on BCCT learning model through art center to develop creativity of 5-6 year old child of Islamiyah Kindergarten. A common problem in this study is